Manipulation through Legal and Judicial Translation Process - Bilero, Anila (Richtmann Publishing, 2012)
In the context of the general translating as a process, that today in the consecutive epoch of globalizing processes who hadinvolved the modern society, the legal and justice translation has been done and he as well as an essential and common; however isclearly visible how little importance and attention, to say the least, is devoted from the criticism or contemporary literature. In translator’senvironments, often we listen the italian expression